Pengaruh Indikator Inklusi Keuangan Terhadap Profitabilitas Bank Konvensional di Indonesia Tahun 2019-2020 - Noviantika Hidayati; Aniek Hindrayani (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
The purpose of this study is to determine the effect of the number of loan accounts, the number of ATMs, and the number of branch offices on the profitability of conventional banks in Indonesia in 2019 - 2022. This research is a quantitative study using the Robust Least Square method regression with Eviews 10. The data collection technique was carried out using secondary data in the form of conventional banking annual reports from 2019 to 2022 totaling 144 samples.. Based on data analysis and discussion, it is concluded that the variable number of loan accounts and the number of ATMs has a negative effect on the profitability of conventional banks, while the variable number of loan offices has a positive effect on the profitability of conventional banks in Indonesia in 2019-2022. Keywords: Loan accounts, ATMs, branches, profitability, conventional banks